Crusher to Mill Transportation Time Calculation—The Aitik Case - Balázs Varannai; Daniel Johansson; Håkan Schunnesson (Minerals, 2022)
Comminution is a major contributor to the production costs in a mining operation. Therefore, process optimization in comminution can significantly improve cost efficiency. The mine-to-mill concept can be utilized to optimize the comminution chain from blasting to grinding. In order to evaluate the mill performance of the ore from a specific location of the deposit, a direct link needs to be established between the mill performance and the place of origin in the mine. Today, technology enables the accurate positioning of drilling, loading, and dumping points in the mine, making the ore flow between loading and crushing more transparent. However, the material flow from the crusher to the mill is not yet fully understood and monitored. This paper presents the development of an ore transportation model, based on the virtual silo concept, between the crusher and the mill for Boliden’s Aitik mine in northern Sweden. The proposed model helps to establish a link between in situ ore location and mill performance. Two transportation time calculations are used, one based on mass balance, and one based on momentary values. Historical data are used to test the capabilities of the model and the results are compared with the transportation time calculated from the mean capacity values, commonly used in previous studies to connect mill parameters with in situ ore location. The comparison of the results show that the mean parameter-based values can be as much as 50% lower than the transportation times, even in normal operation. In the tested times, the transportation time based on momentary values systematically underestimated the cumulated times. The developed model will also serve as a starting point to analyze the effect of geotechnical parameters, in addition to drill and blast design, on the mill performance of the blasted ore.